Avaliação do efeito do beta-cariofileno após status epilepticus induzido por pilocarpina em ratos - Mallmann, Michele Pereira (2023)
Epilepsy is a chronic brain disease characterized by an enduring predisposition to generate epileptic seizures. Epilepsy has serious neurological, cognitive, psychological, and social consequences. Status epilepticus(SE) is a neurological life-threatening condition resulting from the failure of the mechanisms responsible for seizure termination. SE is considered the most extreme form of epileptic seizure with risk of death. It is also associated with significant morbidity and mortality after the event. SE may trigger epileptogenesis and epilepsy. Thus, ceasing SE or attenuate its possible consequences may represent a strategy to prevent epilepsy. Despite numerous advances in medicine, treatment of epilepsy does not prevent its progression, or SE. Epilepsy also has no cure. Natural products may represent a promising source of new antiepileptic drugs. Beta-caryophyllene (BCP) is a sesquiterpene present in many plants. Several studies have demonstrated beneficial effects of BCP in animal models, including the anticonvulsant effect. Thus, we aimed to investigate the effect of BCP on pilocarpine-induced SE. For this, male Wistar rats were used evaluated in two independent protocols. In the first protocol, animals were monitored by video and electroencephalogram (EEG) for 24 h. Rats received BCP (100 mg/kg, i.p), or vehicle, 1h, 8h and 16h after starting SE. Then, animals were evaluated for behavioral recovery and euthanized. Brains were removed for assessment of neuronal damage and albumin infiltration. BCP showed anticonvulsant activity after SE, protecting against more severe epileptic seizures. There was no improvement in the behavioral recovery of the animals BCP-treated, nor a reduction in positive-fluoro jade C neurons in the hippocampus. However, BCP treatment reduced albumin-immunoreactivity in the hippocampus after SE, indicating a protective effect on the blood-brain barrier. In the second protocol, animals were submitted to SE model and treated with BCP (100 mg/kg, i.p) or vehicle, 1h, 8h and 16h after the onset of SE. Different from first protocol, these animals were euthanized seven days after SE induction. Before euthanasia, behavioral tests were performed, brains were removed to assess neuronal damage. BCP improved the motor performance of animals in the Neuroscore test, it also attenuated the neuronal loss in NeuN immunoreactivity. These results show, for the first time, that repeated treatment with BCP prevents the progression of SE within 24 hours after the onset of the event, in addition to exerting a neuroprotective effect. Thus, we believe that BCP deserves more attention as a possible treatment for SE and has great potential to be included as an adjuvant treatment in epilepsy.